2008
DOI: 10.1258/acb.2008.008034
|View full text |Cite
|
Sign up to set email alerts
|

Improving patients' knowledge on the relationship between HbA1c and mean plasma glucose improves glycaemic control among persons with poorly controlled diabetes

Abstract: Background: Recent recommendation advocates the reporting of HbA1c in terms of mean plasma glucose. We examined the impact of improving patients' interpretation of a given HbA1c value on glycaemic control. Methods: We conducted a questionnaire survey among 111 patients attending a hospital diabetes clinic. Patients were provided with information relating to the association between HbA1c and mean plasma glucose levels. Glycaemic control among 80 patients with poor glycaemic control was assessed before and appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
33
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 12 publications
5
33
0
Order By: Relevance
“…It was found that knowledge of HbA1c is poor among diabetic patients. Improvement in understanding of HbA1c is directly related with improvement in glycemic control as reported in other studies [14]. The present study also found that increase in knowledge regarding dietary restrictions and exercise resulted in improvement in glycemic control as reported in other interventions studies aimed at increasing exercise combined with dietary restrictions [15].…”
Section: Discussionsupporting
confidence: 88%
“…It was found that knowledge of HbA1c is poor among diabetic patients. Improvement in understanding of HbA1c is directly related with improvement in glycemic control as reported in other studies [14]. The present study also found that increase in knowledge regarding dietary restrictions and exercise resulted in improvement in glycemic control as reported in other interventions studies aimed at increasing exercise combined with dietary restrictions [15].…”
Section: Discussionsupporting
confidence: 88%
“…HbA1c ≥ 9% is a commonly employed cut-off point indicating uncontrolled glycaemia. (17) At the end of the 24-week follow-up, all patients treated with canagliflozin 300 mg achieved HbA1c < 9% while 42.9% of patients in the sitagliptin 100 mg group still had HbA1c ≥ 9% (Figs. 2a & b).…”
Section: Resultsmentioning
confidence: 96%
“…People need to see the benefits of lifestyle changes, and the knowledge must also simplify and improve life for them [98]. Knowledge alone is thus limited to inducing a person to implement changes in self-care management, unless the person feels motivated.…”
Section: Patient Educationmentioning
confidence: 99%